2010
DOI: 10.2337/dc10-9990
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Type 2 Diabetes

Abstract: Although physical activity (PA) is a key element in the prevention and management of type 2 diabetes, many with this chronic disease do not become or remain regularly active. High-quality studies establishing the importance of exercise and fitness in diabetes were lacking until recently, but it is now well established that participation in regular PA improves blood glucose control and can prevent or delay type 2 diabetes, along with positively affecting lipids, blood pressure, cardiovascular events, mortality,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
1,181
4
96

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,445 publications
(1,305 citation statements)
references
References 289 publications
(494 reference statements)
24
1,181
4
96
Order By: Relevance
“…Our finding supports American Diabetes Association recommendations to increase overall physical activity, including LPA, and reduce sedentary time 5. Previous evidence from the National Health Interview Survey indicated that walking 3 to 4 h/week was associated with up to a 54% reduction in total and CVD mortality in people with diagnosed diabetes mellitus 42.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding supports American Diabetes Association recommendations to increase overall physical activity, including LPA, and reduce sedentary time 5. Previous evidence from the National Health Interview Survey indicated that walking 3 to 4 h/week was associated with up to a 54% reduction in total and CVD mortality in people with diagnosed diabetes mellitus 42.…”
Section: Discussionsupporting
confidence: 88%
“…23,24 Further, targeted exercise programs have been shown to relieve symptoms and comorbidities in adults with Type 2 diabetes regardless of weight loss. 25 Therefore, it is important to examine the phenomenon of abnormal blood glucose in healthy weight individuals and to investigate the effect of physical activity on the blood glucose levels of these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, regular physical activity (PA) is a cornerstone of T2D management due to its major health benefits [10]. Observational data have linked regular PA to improved all-cause mortality, lower rates of cardiovascular disease, lower rates of breast and colon cancer, improved symptoms of depression and anxiety, and better functional outcomes in people with and without T2D [11].…”
Section: Introductionmentioning
confidence: 99%